Copper-Catalyzed Enantioselective Radical Esterification of Propargylic C–H Bonds - Xi, Jiajia; Zhu, Xiaotao; Bao, Hongli (Synthesis, 2024)
The copper-catalyzed enantioselective radical esterification of propargylic C–H bonds with tert-butyl peroxybenzoate (TBPB) as an oxidizing agent and an oxygenated nucleophile is reported. This variant of the Kharasch–Sosnovsky oxidation allows for the asymmetric esterification of open-chain carbon radicals without excessive amounts of alkyne substrates under mild reaction conditions, achieving a one-step conversion of simple alkynes into chiral propargylic esters.
Keywords: enantioselective esterification; propargylic; Kharasch–Sosnovsky oxidation; copper catalysis; radical